Non scholae, sed vitae discimus! - The importance of fields of study for the gender wage gap among German university graduates during labor market entry and the first years of their careers - Braakmann, Nils (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
This paper investigates the gender wage gap among German university graduates in their first job and five to six years into their careers. We find that women earn about 30% less than men at their first job and about 35% less after five to six years. Results from standard decomposition techniques show that 80% of the earnings gap in the first job can be attributed to differences in endowment of which between 74 and 78% are related to different fields of studies. Adding employer information leads to an explained share of about 90% of the earnings gap with fields of study still accounting for about half of the gap. These also play a dominant role in a model without employer information after five to six years, directly explaining between 26 and 33% of the earnings gap. Adding employer information, however, leads to insignificant results. Together with detailed information on experiences after graduation, these variables account for about 44 to 50% of the earnings gap later in the graduates careers.
Keywords: Gender; Wage Gap; Decomposition; 330 Wirtschaft